2016
DOI: 10.1021/acs.jcim.6b00407
|View full text |Cite
|
Sign up to set email alerts
|

MIB: Metal Ion-Binding Site Prediction and Docking Server

Abstract: The structure of a protein determines its biological function(s) and its interactions with other factors; the binding regions tend to be conserved in sequence and structure, and the interacting residues involved are usually in close 3D space. The Protein Data Bank currently contains more than 110 000 protein structures, approximately one-third of which contain metal ions. Identifying and characterizing metal ion-binding sites is thus essential for investigating a protein's function(s) and interactions. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
162
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(185 citation statements)
references
References 19 publications
2
162
0
Order By: Relevance
“…The side chain conformations and backbone geometry of the designed His were compatible with the CTPR fold and with the metal coordination distances observed in protein coordination sites . The potential of the designed site to coordinate metals was validated computationally using the metal ion‐binding site prediction and docking server . Arrays of three CTPR modules were constructed by combination of H‐modules and WT CTPR units (W‐modules), to obtain CTPR3‐WHW and CTPR3‐HWW proteins, with one H module localized at the central repeat or at the N‐terminal repeat, respectively.…”
Section: Figurementioning
confidence: 95%
“…The side chain conformations and backbone geometry of the designed His were compatible with the CTPR fold and with the metal coordination distances observed in protein coordination sites . The potential of the designed site to coordinate metals was validated computationally using the metal ion‐binding site prediction and docking server . Arrays of three CTPR modules were constructed by combination of H‐modules and WT CTPR units (W‐modules), to obtain CTPR3‐WHW and CTPR3‐HWW proteins, with one H module localized at the central repeat or at the N‐terminal repeat, respectively.…”
Section: Figurementioning
confidence: 95%
“…A query of the COACH , Profunc , and MIB servers revealed that SIRV1 Rep has the potential to bind several metal ions using His64, His66, and Glu55 (Table ). Notably, Profunc also predicted homology with structures of metal‐free Rep proteins with significant superposition of the metal‐binding residues.…”
Section: Resultsmentioning
confidence: 99%
“…A query of the COACH [12], Profunc [13], and MIB [14] servers revealed that SIRV1 Rep has the potential to bind several metal ions using His64, His66, and Glu55 (Table I).…”
Section: Prediction Of the Sirv1 Rep Metal-binding Sitementioning
confidence: 99%
“…The interaction of compound 4 with both COX1-1 (2OYU) and COX-2 (3LN1) [11] was carried out using a DockingServer [15].…”
Section: Theoretical Evaluation Of the Interaction Between Compound 4mentioning
confidence: 99%